MEKANISME PENEGAKAN HUKUM TERHADAP HAKIM YANG MELAKUKAN PELANGGARAN KODE ETIK DI MAHKAMAH KONSTITUSI YANG MEMENUHI UNSUR PIDANA (STUDI PUTUSAN NOMOR. 01/MKMK-SPL/II/2017) - Henny Pertiwi Gani; Abdul Gani Abdullah (Fakultas Hukum Universitas Tarumanagara, 2020)
Violation off the code off ethics committed by judges is an act that worsens the image of the judiciary in Indonesia, violations that have the potential to be criminal or just sanctions. More researchs is needed to understand the accountability of judges who violate potentially criminal code of ethics. The type used in this study is normative legal research. Normative legal research is research to examine the application of positive law. Based on existing research, it is found that there are two forms of accountability of judges, the first is criminal responsibility carried out through general courts and the second is professional accountability handled by each of the existing institutions. Judges are proposed to be dismissed and have the opportunity to defend themselves before the Honorary Board of Judges. Based on the results of the honorary council session will determine what sanctions are most suitable with the judge who has violated it. In this form of accountability, hopefully it will provide a deterrent effect and improve the image of the judiciary in Indonesia.